Viking law and order : places and rituals of assembly in the medieval north - Sanmark, Alexandra (Edinburgh University Press, 2018)
Using archaeological evidence, written sources and place-names, this text provides a comprehensive analysis of the Viking legal system and assembly sites, showing that this formed an integral part of Norse culture and identity, to the extent that the assembly institution was brought to all Norse settlements.